Sistema integrado de geoinformação aplicado à vigilância epidemiológica veterinária - Melo, Bruno Rocha de (2013)
Information systems focused on the storage and processing data of animal health are fundamental tools to prove the epidemiological surveillance actions performed by federal, state and municipal government. These softwares promote transparency in the actions performed by defense agencies livestock, given the concerns of importing markets in the acquisition of safe products to its human and animal population. In this context, it was aimed to develop an integrated geoinformation system focused on veterinary epidemiological surveillance, based on structural abstraction of reality, informational and operational processes of the agency's veterinary service of the state of Minas Gerais. The achievement of this research has been structured in four steps: first, the formulation of a theoretical-practical; second, structuring a spatial database as a central data repository; third, developing a geographic information system integrated into the central repository; and fourth, testing and validation practice. The methodology for developing hybrid systems proved effective in a large capillary administrative institution, and the possibility of integration with external databases indicated a new potential for the improvement of agricultural defense. The management system diseases cases and routine immunization (health reports) provided the largest contribution to the primary objectives of veterinary surveillance, with increases in quality and speed of data collection. The Geographic Information System has shown to be effective in the implementation of the tabular data to the space environment, presenting itself as a differential of the proposed system.